Autosomal dominant chronic mucocutaneous candidiasis with STAT1 mutation can be associated with chronic active hepatitis: A case report - Lingling Liu; Yuan Huang; Yi Liao; Sainan Shu (Frontiers in Pediatrics, 2023)
BackgroundChronic mucocutaneous candidiasis (CMC) is a heterogeneous primary immunodeficiency disease characterized by chronic or recurrent Candida infections of the skin, nails, and mucosa and is mostly associated with STAT1 gain-of-function (GOF) mutation (GOF-STAT1 mutation).Case presentationA two-year-old girl was presented with recurrent liver dysfunction, oral candidiasis, acute bronchial pneumonia, and cytomegalovirus infection. Even after a series of treatments, including antifungal voriconazole, nystatin treatment for oral Candida, antibiotics against bacterial infection, and bicyclol to protect the liver, the child still exhibited signs of splenomegaly. Although we performed relevant etiological tests on the child and conducted histopathology and electron microscopic examination of the liver, we could not explain the clinical symptoms. So, a genetic test was conducted to clarify the diagnosis. Since the child suffered recurrent fungal infections, we speculated that she had combined immunodeficiency. Therefore we performed high-precision clinical display PLUS detection and found that the transcription factor STAT1 had a heterozygous GOF mutation (p. R274W) in its coiled-coil domain.ConclusionThe clinical manifestations of chronic mucocutaneous candidiasis caused by GOF-STAT1 mutations are complex and range from mild local fungal infections to severe systemic diseases and are sometimes fatal. Clinicians need to be aware of the possibility of this disease in children with recurrent fungal infections for early diagnosis and treatment.